ANALYSIS OF EXPRESSION OF IMPLICATURE THROUGH FIGURATIVE DEVICES IN AMERICAN LITERATURE (Scientific journal of the Fergana State University, 2023)
Implied speaker meaning which is called Implicature in Pragmatics finds various ways to be expressed in American Literature. Figurative devices that play role in conveying implied speaker meaning are under analysis in the given article. Metaphor, Simile, Personification, Irony, Illusion, Symbolism are among common figurative devices that vividly express implicature in literary text.